2011
DOI: 10.1080/03634523.2010.487111
|View full text |Cite
|
Sign up to set email alerts
|

Students' Talk about the Climate of Feedback Interventions in the Critique

Abstract: Similar to many courses in communication, oral communication is central to the learning goals in the discipline of design. Design critiques, the primary communication activity in design classrooms, occur in every studio course multiple times. One key feature of the critique, as an oral genre, is the amount of time and emphasis placed on feedback. The feedback intervention process within the critique plays a large role in determining the overall communicative climate of the teaching and learning event. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Related to the research on feedback, there is a growing body of research on the influence of critique, and especially peer critique, on creativity in art and design education (e.g.. Budge, Neale, & Lynas, 2013;Dannels, Housley Gaffney, & Norris Martin, 2011;Gray, 2013;Percy, 2004;Schrand & Eliason, 2012). For example.…”
Section: In-process Critiquementioning
confidence: 99%
“…Related to the research on feedback, there is a growing body of research on the influence of critique, and especially peer critique, on creativity in art and design education (e.g.. Budge, Neale, & Lynas, 2013;Dannels, Housley Gaffney, & Norris Martin, 2011;Gray, 2013;Percy, 2004;Schrand & Eliason, 2012). For example.…”
Section: In-process Critiquementioning
confidence: 99%
“…As we think of improving design reviews for students, it is important to recognize the diversity of student experience in design reviews: there are several different modes of interaction among students and reviewers (Frederickson, 1990), and even students who describe their experiences of design review climate similarly had different affective outlooks on that climate (Dannels et al, 2011). These findings indicated that there are elements of design reviews that affect student experience beyond attitudes or actions alone.…”
Section: Feedback In Design Reviewsmentioning
confidence: 93%
“…More recently, the drive for deeper understanding of the role of feedback in design reviews has included a series of papers by Dannels, Housley Gaffney, and Martin which identified common types of design review feedback , explored the deeper meanings of feedback beyond its relationship to a project (Dannels, Housley Gaffney, & Martin, 2008), and examined student perspectives on how feedback contributed to design review climate (Dannels, Housley Gaffney, & Martin, 2011). Central to this research was a critical approach to analyzing design review communication, where feedback was considered as a communication tool for both project and relational information.…”
Section: Feedback In Design Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedback interventions have been studied in a variety of situations within higher education, such as the performance of college students in design studios (Dannels, Housley Gaffney & Norris Martin, 2011) and for students who were mandated to undergo a substance abuse program due to violations of alcohol or drug policies in their residence halls (Mun, White & Morgan, 2009;Lojewski, Rotunda & Arruda, 2010). Mun, White, and Morgan (2009) used both written and motivational interviewing as feedback interventions to determine if gender differences existed for each strategy for students mandated to participate in alcohol assistance programs after violating college alcohol policies.…”
Section: Individual Interventions In Higher Educationmentioning
confidence: 99%